Deconstructing the kiasu parent in Singapore - Amirah Arip (2013)
There has been much furore in the recent years about kiasu parents who pile up their children’s time with enrichment classes leading to young children feeling stressed out and losing their childhood. This study seeks to rationalize the stereotypical images of the Singaporean kiasu parent using the structural-educational context of Singapore. I will also bring in new perspectives of childhood, such as the notion of the Athenian child, to explain their motivations to put pressure on their children at an early age despite their hesitations for doing so. I argue that parents are reflexive actors who do not simply hothouse their children for academic success but negotiate definitions of success in Singapore the best they can.